Solar cell stacked dual‐polarised patch antenna for 5.8 GHz band WiMAX network. Issue 24 (1st November 2013) - Yurduseven, O.; Smith, D.
Abstract : A novel combination of a two‐port slant ± 45° dual‐polarised microstrip patch antenna with a polycrystalline silicon (poly‐Si) solar cell operating as an RF stacked parasitic patch element is presented and discussed for 5.8 GHz band polarisation diverse multifunctional WiMAX systems. To minimise the effect of the solar operation on the RF antenna performance, an effective DC/RF isolation circuit consisting of quarter‐wavelength microstrip transmission lines is demonstrated. The proposed solar patch provides identical E ‐plane and H ‐plane far‐field radiation patterns for +45° and −45° polarisations with a gain of 7.8 dBi and operates at the frequency band of 5.66–5.91 GHz.